Targeted health promotion with guided nature walks or group exercise: a controlled trial in primary care - Kolster, Annika; Heikkinen, Malin; Pajunen, Adela; Mickos, Anders; Wennman, Heini; Partonen, Timo (Frontiers in Public Health, 2023)
Background Contact with nature promotes human wellbeing through diverse pathways, providing a potential way to support health especially in primary care, where patients commonly suffer from multimorbidity and poor general health. Social prescribing as a non-pharmaceutical treatment is a promising method to improve health as well as inclusion. This study explores and compares the effects of a nature based and an exercise based social prescribing scheme on mental wellbeing and sleep, in a primary care population. Methods Primary care patients identified to benefit from general health improvement were recruited by nurses, doctors, or social workers to this non-randomized, intention-to-treat, pilot study. Participants (n=79) chose between two group interventions, either taking part in guided walks in nature, including immersion in a forest with high biodiversity, or participating in a versatile sports program. Mental wellbeing was assessed with the Warwick-Edinburgh Mental Well-Being Scale (WEMWBS), with additional questions evaluating self-rated health and sleep. Impact on mental wellbeing was explored in relation to perceived health. The amount and quality of sleep was measured with wrist-worn accelerometers. With a focus on everyday life impacts, the assessments took place before and after the 8-week intervention. All participants lived in Sipoo, Finland, an area with abundant accessible green space. Results Participants (mean age 57 years, 79% female) rated their general and mental health lower than the general population. Participation in the Nature-group improved mental wellbeing (change in WEMWBS by 3.15, p=0.008), with positive change for feeling of being relaxed, being cheerful, having energy to spare, feeling of dealing well with problems, feeling good about oneself and feeling of being close to other people. The Sports-group was beneficial only for those initially rating their health as good. Sleep duration improved in the Sports-group, while participants in the Nature-group reduced time awake after sleep onset and reported better sleep quality. Following the intervention perceived health, functional ability improved in both groups, perceived mental health in the Nature-group. Conclusions We attest that even where surroundings are green, active interventions can further improve health in a primary care population, and that nature-based social prescribing is favourable for those in poor health.